Impact of drug price adjustments on utilization of and expenditures on angiotensin-converting enzyme inhibitors and angiotensin receptor blockers in Taiwan - Huang, Shiou-Huei (BioMed Central, 2012)
BACKGROUND: A previous study has suggested that drug price adjustments allow physicians in Taiwan to gain greater profit by prescribing generic drugs. To better understand the effect of price adjustments on physician choice, this study used renin-angiotensin drugs (including angiotensin-converting enzyme inhibitors [ACEIs] and angiotensin receptor blockers [ARBs]) to examine the impact of price adjustments on utilization of and expenditures on patented and off-patent drugs with the same therapeutic indication. METHODS: Using the Taiwan’s Longitudinal Health Insurance Database (2005), we identified 147,157 patients received ACEIs and/or ARBs between 1997 and 2008. The annual incident and prevalent users of ACEIs, ARBs and overall renin-angiotensin drugs were examined. Box-Tiao intervention analysis was applied to assess the impact of price adjustments on monthly utilization of and expenditures on these drugs. ACEIs were divided into patented and off-patent drugs, off-patent ACEIs were further divided into original brands and generics, and subgroup analyses were performed. RESULTS: The number of incident renin-angiotensin drug users decreased over the study period. The number of prevalent ARB users increased and exceeded the cumulative number of first-time renin-angiotensin drug users starting on ARBs, implying that some patients switched from ACEIs to ARBs. After price adjustments, long term trend increases in utilization were observed for patented ACEIs and ARBs; a long-term trend decrease was observed for off-patent ACEIs; long-term trend change was not significant for overall renin-angiotensin drugs. Significant long-term trend increases in expenditures were observed for patented ACEIs after price adjustment in 2007 (200.9%, p = 0.0088) and in ARBs after price adjustments in 2001 (173.4%, p < 0.0001) and 2007 (146.3%, p < 0.0001). A significant long-term trend decrease in expenditures was observed for off-patent ACEIs after 2004 price adjustment (−156.9%, p < 0.0001). Expenditures on overall renin-angiotensin drugs showed long-term trend increases after price adjustments in 2001 (72.2%, p < 0.0001) and 2007 (133.4%, p < 0.0001). CONCLUSIONS: Price adjustments did not achieve long-term cost savings for overall renin-angiotensin drugs. Possible switching from ACEIs to ARBs within individuals is evident. Policy makers should reconsider the appropriateness of the current adjustment strategies applied to patented and off-patent drugs.